Interprofessional Team-Based Learning: Medical Students and Nursing Students Discussing Medical Error Together - Julia Belkowitz; Terry Eggenberger; Kathryn Keller; Amy Zito; Gauri Agarwal (Association of American Medical Colleges, 2014)
Abstract This is an interprofessional team-based learning session created for medical students and nursing students. The session includes discussion about and ethical issues related to medical error prevention and disclosure. This two-hour session provides the opportunity for the two groups of students to collaboratively work through clinical scenarios in which medical errors take place, and identify shared approaches to these important issues. We have run this session three times with different groups of third-year medical students and nursing students in both accelerated and traditional track programs. Each session has provided the opportunity for rich discussion within the group. The readings and cases also allow students to learn about commonalities and differences between the two disciplines and the professional codes they follow.